A Histone H2A Deubiquitinase Complex Coordinating Histone Acetylation and H1 Dissociation in Transcriptional Regulation - Zhu, Ping (2007)
Deciphering the epigenetic “code” remains a central issue in transcriptional regulation. Here, we report the identification of a MPN(+)/JAMM domain-containing histone H2A deubiquitinase (2A-DUB, or KIAA1915/MYSM1) specific for monoubiquitinated H2A (uH2A), that has permitted delineation of a strategy for specific regulatory pathways of gene activation. 2A-DUB regulates transcription by coordinating histone acetylation and deubiquitination, and destabilizing the association of linker histone H1 with nucleosomes. 2A-DUB interacts with p/CAF in a co-regulatory protein complex, with its deubiquitinase activity modulated by the status of acetylation of nucleosomal histones. Consistent with this mechanistic role, 2A-DUB participates in transcriptional regulation events in androgen receptor-dependent gene activation, and the levels of uH2A are dramatically decreased in prostate tumors, serving as a cancer-related mark. We suggest that H2A ubiquitination represents a widely-used mechanism for many regulatory transcriptional programs, and predict that various H2A ubiquitin ligases/deubiquitinases will be identified for specific cohorts of regulated transcription units.